Grb2-associated binder 1 (Gab1) genetic polymorphism, Helicobacter pylori infection, and chronic atrophic gastritis among older adults from Germany - Gao, Lei; Weck, Melanie N.; Nieters, Alexandra; Brenner, Hermann (Molecular carcinogenesis, 2010)
Grb2‐associated binder 1 (Gab1) plays an important role in the regulation of cell growth and transformation. A single nucleotide polymorphism (SNP) (rs3805246) in the Gab1 gene has been suggested to be related to the risk of Helicobacter pylori infection and chronic atrophic gastritis (CAG) in a study from Japan. We aimed to assess the associations in a population‐based study from Germany. In the baseline examination of ESTHER, a population‐based study conducted in Saarland, serum pepsinogen I and II and H. pylori serostatus were measured by ELISA. The Gab1 SNP (rs3805246) was genotyped in 351 serologically defined CAG cases and 351 age‐ and sex‐matched non‐CAG controls. A nonsignificant association was observed between the Gab1 SNP and CAG, with an adjusted odds ratio of 1.15 (0.85–1.55) for AA/AG carriers compared to GG carriers. The magnitude of the association did not change when the analysis was restricted to H. pylori seropositive subjects. Furthermore, no significant relation was found between the SNP and H. pylori seropositivity among non‐CAG controls. We could not confirm a major association between Gab1 SNP (rs3805246) and the predisposition to H. pylori infection and CAG in this study population from Germany. Further studies with larger sample size are needed to clarify a potential modest effect of Gab1 genetic polymorphisms. © 2010 Wiley‐Liss, Inc.